PRINSIP-PRINSIP EKONOMI ALQURAN - Ruslan Ruslan (At-Taradhi Jurnal Studi Ekonomi, 2012)
This article uses historical, philosopical and legal approaches. It is historical for it traceseconomic activities back to the time of prophet Adam until prophet Muhammad. It is at the sametime, philosopical and legal in nature because there are discussions on some Quranic precepts oneconomy that need to be obliged. The four principles of Quranic economy are tauhid, balance,free will and responsibility. Starting from tauhid, a Muslim believes that his prayers and devotions,his life and death are only for Gods sake. With balance, it is expected that no inflation, economicrecession and depression occur. With free will and responsibility, economic actors are expected towork hard and execute Gods mandates.